2010
DOI: 10.1016/s0030-6657(10)70023-8
|View full text |Cite
|
Sign up to set email alerts
|

Uchyłki przedniej ściany gardła po laryngektomii całkowitej

Abstract: This study indicates that leaving hyoid bone is a major risk factor for developing pseudoepiglottis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They found no association with tumor size, the addition of neck dissection, or post‐operative radiotherapy. Further studies have confirmed these findings 8,21 . Fistula formation has also been disproved as a cause of pseudo‐epiglottis 2,6,22,23 …”
Section: Discussionmentioning
confidence: 87%
“…They found no association with tumor size, the addition of neck dissection, or post‐operative radiotherapy. Further studies have confirmed these findings 8,21 . Fistula formation has also been disproved as a cause of pseudo‐epiglottis 2,6,22,23 …”
Section: Discussionmentioning
confidence: 87%
“…Lippert et al also noted correlation between neo-vallecula formation and neopharyngeal closure, with 67% of reported T-type closure patients and 100% of longitudinal closure patients developing a neo-vallecula [ 8 ] ( Table 1 ). In contrast with the above, some studies have found no correlation between neo-vallecula and closure technique, pharyngocutaneous fistula incidence, or radiotherapy [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%